PENGEMBANGAN BUDAYA KEWIRAUSAHAAN BERBASIS SYARIAH UNTUK MENCIPTAKAN PENGUSAHA DARI LINGKUNGAN SANTRI PADA PONDOK PESANTREN DI KABUPATEN JEMBER - Sunarsih Sunarsih; Ratih Rahmawati; Bagus Qomaruzzaman (RELASI : JURNAL EKONOMI, 2013)
Development of an entrepreneurial culture based on Islamic boarding school is an important part in the economic life of the people, especially in growing businesses of the neighborhood students, who have distinctive characteristics: honesty, risk-taking, hard-never give up, and independent.In order to optimize the development of the regional economy Jember, the development of an entrepreneurial culture to create a Sharia-based environmentalentrepreneurs from Boarding School in Jember more effective and relevant for the study, because the district. Jember city known as students save a lot of potential support for accelerated development of Sharia-compliant forward. Identifying the purpose of this study sharia-based entrepreneurial ability, the boarding school in Jember. Research utilizing primary and secondary data from the Department of Cooperatives and related agencies as well as the spread of structured questionnaires to the respondents. Determined that respondent knowingly 9 boarding schools that have received program package C/SMA equivalent and approved by the Office of Religious Affairs of data analysis using methods Turla and Hawkins.